Phytochemistry and Pharmacological Activities of Wolfiporia cocos (F.A. Wolf) Ryvarden & Gilb - Anzheng Nie; Yanhui Chao; Xiaochuan Zhang; Wenrui Jia; Zheng Zhou; Chunsheng Zhu (Frontiers in Pharmacology, 2020)
Poria cocos is the dried sclerotium of Wolfiporia cocos (F.A. Wolf) Ryvarden & Gilb., which was the current accepted name and was formerly known as Macrohyporia cocos (Schwein.) I. Johans. & Ryvarden, Pachyma cocos (Schwein.) Fr., Poria cocos F.A. Wolf and Sclerotium cocos Schwein. It is one of the most important crude drugs in traditional Chinese medicine, with a wide range of applications in ameliorating phlegm and edema, relieving nephrosis and chronic gastritis and improving uneasiness of minds. Its extensive pharmacological effects have attracted considerable attention in recent years. However, there is no systematic review focusing on the chemical compounds and pharmacological activities of Poria cocos. Therefore, this review aimed to provide the latest information on the chemical compounds and pharmacological effects of Poria cocos, exploring the therapeutic potential of these compounds. We obtained the information of Poria cocos from electronic databases such as SCI finder, PubMed, Web of Science, CNKI, WanFang DATA and Google Scholar. Up to now, two main active ingredients, triterpenes and polysaccharides of Poria cocos, have been identified from Poria cocos. It has been reported that they have pharmacological effects on anti-tumor, anti-bacterial, anti-oxidant, anti-inflammatory, immunomodulation, and liver and kidney protection. The review summarizes the phytochemistry and pharmacological properties of Poria cocos, which suggest that researchers should focus on the development of new drugs about Poria cocos to make them exert greater therapeutic potential.